2022
DOI: 10.1128/jcm.01717-21
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of SARS-CoV-2 Antibody Detection Assays against S and N Proteins among Pre-COVID-19 Sera from Patients with Protozoan and Helminth Parasitic Infections

Abstract: We aimed to assess the specificity of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibody detection assays among people with tissue-borne parasitic infections. We tested three SARS-CoV-2 antibody-detection assays (cPass SARS-CoV-2 neutralization antibody detection kit [cPass], Abbott SARS-CoV-2 IgG assay [Abbott Architect], and Standard Q COVID-19 IgM/IgG combo rapid diagnostic test [SD RDT IgM/SD RDT IgG]) among 559 pre-COVID-19 seropositive sera for several parasitic infections.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In a group of sera taken before the COVID-19 pandemic from patients seropositive for parasitic infections (leishmaniasis, malaria, Chagas disease), the presence of cross-reactive antibodies has been observed in assays for the detection of anti-SARS-CoV-2, suggesting that in regions with the coexistence of these pathogens, false positive cases could occur due to cross-reactivity in a wide variety of serological tests [21]. The cross-reactivity of antibodies we observed is drastically reduced with the use of synthetic peptides in the ELISA assay and is not evident when these antibodies are tested by Western Blot assay, suggesting that cross-reacting antibodies mainly recognise conformational and non-sequential epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…In a group of sera taken before the COVID-19 pandemic from patients seropositive for parasitic infections (leishmaniasis, malaria, Chagas disease), the presence of cross-reactive antibodies has been observed in assays for the detection of anti-SARS-CoV-2, suggesting that in regions with the coexistence of these pathogens, false positive cases could occur due to cross-reactivity in a wide variety of serological tests [21]. The cross-reactivity of antibodies we observed is drastically reduced with the use of synthetic peptides in the ELISA assay and is not evident when these antibodies are tested by Western Blot assay, suggesting that cross-reacting antibodies mainly recognise conformational and non-sequential epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, the detected antibodies test negative in neutralization assays. 13,14 However, they may be a marker of a much broader immune response that includes both humoral and cellular features. Pre-existing T-cell immunity and its potential role in ameliorating clinical course in SARS-CoV-2 infection is another hotly debated issue.…”
Section: Discussionmentioning
confidence: 99%
“…We did not consider neutralizing antibody assays, as it has been clearly shown that detected antibodies in pre-pandemic African samples typically do not have neutralizing capacity. 13,14…”
Section: Methodsmentioning
confidence: 99%
“…It has also been suggested that cross-reactivity with parasitic infections could lower the specificity of COVID-19 serology testing. A study investigated the impact of helminth infections on the specificity of three different SARS-CoV-2 antibody detection assays, which were tested on 559 serum samples collected before July 2019 and known to be seropositive for several parasitic infections [ 114 ]. Although the authors found that the specificity of the 50 sera samples with Strongyloides seropositivity was preserved, there was a lower specificity found in the specimens seropositive for visceral leishmaniasis and African trypanosomiasis.…”
Section: Impact Of Strongyloides On Covid-19mentioning
confidence: 99%